The concepts of autonomy, privacy and informed consent in nursing - Lemonidou, Chryssoula; Kapela, M; Panagiotou, A; Arndt, Marianne; Dassen, Theo; Gasull, Maria; Scott, Philomena Anne; Välimäki, Maritta; Leino-Kilpi, Helena; Merkouris, Anastasios (My University, 1993)
The concepts of autonomy, privacy and informed consent in nursing. In this article a research program is presented being funded by the European Union. The program has been organized and will be implemented by Universities of five European countries: Finland, England, Germany, Greece and Spain. Purpose of the study is: 1) to develop a common knowledge base concerning the concepts of autonomy, privacy and informed consent, 2) to determine and describe the differences and problems in implementing these contents between these five countries. Methods: The sample will include patients and nurses from surgical and maternity wards as well as elderly patients (over 65) from long term care facilities. The study includes two phases: 1) review of theoretical and empirical data and development of a questionnaire, 2) collection and analysis of study data. Conclusion: The goal is to en-chance ethical knowledge base for nursing professionals in order to maintain Righ ethical standards in nursing and to improve the quality of nursing and health care in Europe.